Seed Characterisation of Five New Pomegranate (Punica Granatum L.) Varieties - Amit Parashar (International Journal of Pharma and Bio Sciences, 2010)
This study evaluated the production of ï¬ve new pomegranate varieties (MAP 14 , AKP15 , DMWP 2, NMRP 7 and JBP 1), being all indigenous to Southeastern India where the species shows high variability. A morphological and organoleptic characterisation of the edible portion of the seeds were investigated. Some chemical characteristics of the juice, including total soluble solids, pH, acidity and maturity index, were assessed. Morphological characteristics of both the edible and the woody portions of the seed were evaluated. Also productive and organoleptic characteristics of all varieties were considered, being MAP 14 and AKP 15 the highest yielders. Furthermore, DMWP 2 and JBP 1 showed the heaviest seeds (both showing an average weight of 0.61 g) while AKP 15 the lightest one (0.37 g). Regarding seed juice content, there were signiï¬cant differences among the evaluated varieties; whereas DMWP 2 and JBP 1 showed the highest juice contents, NMRP 7 yielded the lowest one. However, the cultivar NMRP 7 showed a signiï¬cantly higher acidity content than the others, along with the lowest maturity index at all. Finally, MAP 14 and AKP 15 were very interesting because of their high production, large fruit size and excellent seed organoleptic characteristics.